A comparison between the values obtained from active drag analysis compared to forces produced in tethered swimming - Mason, B.; Formosa, D.; Rollason, S. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to identify in a maximum swim effort by elite freestyle swimmers, if the mean force produced in tethered swimming over a set number of whole strokes could reliably be utilised as an alternative measure for mean propulsive force over the same number of whole strokes. Tethered force can be measured relatively easily. Although mean propulsive force at a maximum swim velocity may be derived, the process of doing so is not direct, is time consuming and requires an extensive setup. Stepwise regression analysis indicated that mean tethered force was not an acceptable alternative for mean propulsive force. Therefore the use of mean propulsive power to monitor training would require the measurement of mean propulsive force rather than simply measuring the mean tethered force in a maximum swim effort.